The Use of Animation Movies for Developing Students’ Writing Skill of Narrative Texts at Ninth Grade Students of SMP Negeri 13 Binjai - Alfiani, Netty (Pascasarjana Universitas HKBP Nommensen, 2020)
English is an international language, which is spoken in international events and is used as the medium of transferring information flow on science, technology, and culture as well. As a matter of fact, students should be able to perform language skill such as listening, speaking, reading and writing. But for the students, writing is the most difficult subject. That is why the curriculum 2013 of Junior High School emphasizes more on developing students’ writing skill. The objectives of the study are; to know what the students’ difficulties in understanding a narrative text and to know to what extent teaching writing of a narrative text can improve students’ writing skill. The research will give some useful information about a narrative text and teaching writing by using afilm Moana. It will be more interesting for the students to produce a narrative text by listening the dialogue of the film. The techniques of collecting data were by using tests. An interview was also done to know students’ difficulties in producing a narrative text faced by the students. The result of the tests shows that the students’ scores in the writing draft I were 64, 3%. It means that the test was not successful. On the other hand, in the writing of the revision II, the students’ achievement reached 72, 9%. It means that the test was successful.